Scenografi för en landskapsarkitekt - Grundberg, Julia (2007)
Stage Design is design for action and contains décor, side-scenes and properties, as well as costume and grease-paint. The one responsible for this is the Stage Designer, who together with the Director, creates the best conditions for the actors to perform in. The stage, where the play takes place, could be either in a theater, an auditorium, or in another sort of room, at another place, inside or outside, and where the place itself inspires to theatrical performance and expressions. This type of theater is called Site-specific theatre. Two examples of this is the workshop "Skogen sjunger" (eng. "The forest sings") and the outdoor stage-setting "Odysséen som Nausikaa fick höra" (eng. "The Odyssey which Nausikaa heard"). In "Skogen sjunger", sound in proportion to place, from which the sounds arose, was investigated. In "Odysséen som Nausikaa fick höra" the Director and the Stage Designer used the landscape and wanted to recreate different places, in the play's tale, which the audience should meet in the landscape. The tale and the landscape should complement and strengthen each other either figuratively, emotionally or spatially.